Feiras livres como organizações policrônicas: Temporalidade nas ações organizativas de feirantes do município de Uberlândia/MG - Reis, Sarentaty Inês Karoline Santana dos (2024)
Contextualization: Both locally and regionally, street markets are characterized as a cultural space that maintains the tradition of interaction and urban coexistence in the streets. They also contribute to trade activities, and job and income generation. In the city of Uberlândia, Minas Gerais, there are 76 street markets that take place fromTuesday to Sunday in various neighborhoods (36 during daytime and 40 at night) and offer a variety of products and prices. Objective: The research was guided by the following question: How do the organizational experiences of street vendors in street markets generate different ways of interpreting and constructing organizational temporality? The objective of this understand is to analyze the temporality of the experiences lived by the street vendors at work in street markets in Uberlândia, Minas Gerais, based on the types: temporary, intermittent, transitory, and ephemeral. The theoretical references that underlie this research are studies about time in philosophy, sociology, history, and studies on temporality in organizational management. Method: From a qualitative approach of the researched material and principles of ethnomethodology, the data collection was carried out using the narrative interview with the stallholders, the photographic record of the organizational processes employed by the stallholders and field notes of the events/situations observed in the field research.The research categories are: (1) trajectory of the stallholders and lived experiences; (2) organization of daily practices and people involved in the management of the business; (3) planning of participation in the fair and expectations for the future; (4) context and economic, social and political interactions between the stallholders, between them and customers, suppliers and also with the government (frequency, themes and objective/reasons for interactions). Results: The street markets are approached as a form of social organization, because, although they are not organizations in the traditional sense of industrial bureaucracies, they constitute a fluid organizational form of territorial occupation and can also be understood from the point of view of organizational management. In organizational and strategy studies, organizations are classified in different ways, giving rise to different organizational types. From a perspective of organizational temporality, some types have already been identified: temporary, intermittent, ephemeral and transitory. The results of the research contribute to studies on organizational temporality, presenting a new type called “Polychronic Organizations”: those characterized by multiple temples. Adherence of the research with the area of concentration of the PPGAdm (Regionality and Management) and with the line of research: The street markets are analyzed in the research as fluid organizations, with practices and processes specific to this organizational form of local and regional commerce. Expanding knowledge about this organizational dimension of the management of street markets is adherent to the line of research. Impact and innovative character in intellectual production: The research contributes with a new type that expands the current typology on organizational temporality, reinforcing existing notions of organizational temporality and showing a new type of temporality in organizational management. Economic, social and regional impact: The street markets analyzed in the research are social, cultural and economic agents with a significant presence in the city’s neighborhoods and regional interconnections. The research brings results that contribute to future municipal public policy actions. Regional implications: The street markets have a weekly presence in the lives of residents of the city’s neighborhoods and in the offer of products from family (and non- family) production to local street commerce. The research contributes to the studies of the organizational practices of market stallholders in the city of Uberlândia, Minas Gerais, and their relationship with the organizational temporality – past, present and future in the creation, maintenance and transformation of this traditional form of commerce. Sustainable Development Goals met in the survey: This study on street markets contributes to SDG 8 – Decent work and economic growth, specifically with goal 8.3 – promote development-oriented policies that support productive activities, generation of decent employment, entrepreneurship, creativity and innovation, and encourage the formalization and growth of micro, small and medium-sized enterprises, including through access to financial services.